Caracterização do uso da terra em diferentes épocas na bacia hidrográfica do ribeirão paraíso- são manuel sp, por meio de sistemas de informações geográficas - Pollo, Ronaldo Alberto [UNESP]; Barros, Zacarias Xavier de [UNESP]; Garcia, Yara Manfrin [UNESP]; Silveira, Gabriel Rondina Pupo da [UNESP]; Nardi, Rafael Calore [UNESP] (EIA Energy in Agriculture, 2014)
This study aimed to evaluate a period of 38 years, the use and soil occupation of the Paradise River watershed, inserted in the citys of São Manuel and Areiópolis-SP using aerial photographs for the year 1972 and TM image (Thematic Mapper) obtained by the Landsat-5 satellite, in 2010, using geoprocessing techniques. The watershed in question is very important for the city of São Manuel-SP, because its urban area is inserted in its divisors which part of it belongs to the Environmental Protection Area (APA) Perimeter Botucatu-SP, considered a recharge area of the aquifer Guarani. Today, the development of agriculture faces challenges, which is to produce more food without impacting the environment. Allied to this concern, research institutions have sought new technologies that allow the detection and quantification of human actions, enabling interventions in order to minimize possible damage to the environment. Among these technologies can be cited Geographic Information Systems (GIS), which a large volume of data and information stored in a region at different times can be evaluated in the same time, suggesting different approaches to the planning of land use. The results of the mapping of areas of use and soil occupation result nine classes in 1972, and the coffee culture showed the biggest occupation (37.94%) of the total area. The 2010 mapping formulated twelve classes of use, which demonstrated the predominance of sugar cane (37.94%), on the areas occupied by coffee and pasture before. The land use maps of 1972 and 2010 showed results that show intense human activity in the modification of natural landscape.

O presente trabalho teve como objetivo avaliar num período de 38 anos, o uso e ocupação do solo da bacia hidrográfica do ribeirão Paraíso, inserida nos municípios de São Manuel e Areiópolis-SP, por meio de fotografias aéreas referente ao ano de 1972 e imagem TM (Thematic Mapper) obtida pelo satélite Landsat-5 de 2010, utilizando-se de técnicas de geoprocessamento. A bacia em questão representa grande importância para a cidade de São Manuel-SP, pois sua área urbana está inserida em seus divisores onde parte da mesma pertence a Área de Proteção Ambiental (APA) Perímetro Botucatu-SP, considerada uma área de recarga do Aquífero Guarani. O desenvolvimento da agricultura nos dias atuais enfrenta desafios, qual seja produzir mais alimentos sem causar impactos ao meio ambiente. Aliados a esta preocupação, as instituições de pesquisa tem buscado novas tecnologias que permitem a detecção e quantificação das ações antrópicas, possibilitando intervenções no intuito de minimizar possíveis danos causados ao meio ambiente. Entre estas tecnologias podem ser citados os Sistemas de Informações Geográficas (SIGs), onde um grande volume de dados e informações armazenadas de uma região em diferentes épocas pode ser avaliado simultaneamente, sugerindo diversas abordagens sobre o planejamento do uso do solo. Os resultados do mapeamento das áreas de uso e ocupação do solo totalizaram nove classes em 1972, sendo a cultura cafeeira a qual apresentou maior ocupação (37,94%) da área total. O mapeamento de 2010 apresentou doze classes de uso, onde se constatou a predominância da cultura canavieira (48,25%), sobre as áreas antes ocupadas por café e pastagem. Os mapas de uso do solo de 1972 e 2010 apresentaram resultados que evidenciam intensa ação antrópica na modificação da paisagem natural.
Description of land use in different times in stream paraíso watershed-são manuel (sp) using sig.
Keywords: Geographic information system; Watershed; Land use.; Sensoriamento remoto; Bacia hidrográfica; Uso e ocupação do solo; Sistemas de informações geográficas.